'An Explosion of Vitality and Creativity'? Memory and Historiography of the Second World War in Belgium and the Netherlands. (1st March 2013) - Mertens, Bram
<x xml:space="preserve">Abstract</x> The construction of narratives of the Second World War and its aftermath in the Netherlands and in Belgium is investigated, both in public opinion and amongst historians. The argument is presented that a popular public consensus about the War in the Netherlands, actively supported by the government, was developed immediately after the war and remained in place until it was challenged by historians in the eighties. In Belgium, on the other hand, political turmoil in the immediate post-war years stood in the way of a similar consensus developing. Instead, a specific Flemish counter-narrative was developed in Catholic and nationalist circles, which came to dominate public discourse in Belgium until it too was challenged in the eighties.